Phytosociological Survey and Weed Interference in Eggplants Cultivation1 - MARQUES,L.J.P. (2016)
ABSTRACT Eggplants are vegetables of great importance in the South and Southeast regions of Brazil, which are subject to interference from weeds. In order to collaborate with weed management in this vegetable, this study was carried out to determine the periods of weed interference in growing eggplants. The study was conducted in the Brazilian municipality of Jaboticabal, SP, at the Faculty of Agricultural and Veterinary Sciences, UNESP [Universidade Estadual Paulista "Júlio de Mesquita Filho" (São Paulo State University)], in the period from February to July 2013. The experiment was arranged in a randomized block design with 22 treatments, three replications divided in 11 periods of coexistence and weed control with eggplants: 14, 28, 42, 56, 70, 84, 98, 112, 126, 140 and 154 days after transplanting (DAT). In each treatment, a phytosociological study was carried out to identify the important species of weeds in eggplant crops. The main weeds were Eleusine indica, Nicandra physaloides, Portulaca oleracea and Cyperus rotundus due to their high relative importance. The interference of these weeds caused losses of up to 96% to the standard commercial fruit yield. The period before interference was 6 DAT and the total period of interference was 102 DAT. Therefore, it is concluded that after the initial six days after transplanting eggplants, the crop should be free of weeds within the next 96 days.